Possible Superconductivity Transition in Nitrogen‐Doped Lutetium Hydride Observed at Megabar Pressure - Xingbin Zhao; Yu Huang; Shuailing Ma; Hao Song; Yanwei Cao; Hao Jiang; Yanping Huang; Tian Cui (Advanced Science)
Abstract The pursuit of room‐temperature superconductivity at an accessible synthetic pressure has been a long‐held dream for both theoretical and experimental physicists. Recently, a controversial report by Dasenbrock‐Gammon et al. claims that the nitrogen‐doped lutetium trihydride exhibits room‐temperature superconductivity at near‐ambient pressure. However, many researchers have failed to independently reproduce these results, which has sparked intense skepticism on this report. In this work, a LuH2±xNy sample is fabricated using high‐pressure and high‐temperature methods. The composition and structural characterization are the same as the aforementioned near‐ambient superconductor. In situ X‐ray diffraction investigations indicate that a high‐pressure phase transition toward Fm3¯m‐LuH3±xNy occurred in the sample at 59 GPa. The temperature‐dependent resistance measurements reveal that two possible superconductivity transition are observed at 95 GPa, with Tc1 ≈6.5 K for high‐Tc phase and Tc2 ≈2.1 K for low‐Tc phase, arising from the disparate phases in the sample. Resistivity measurements in the Fm3¯m‐LuH3±xNy phase under varying magnetic fields exhibited characteristics consistent with superconductivity, with an upper critical field μ0Hc2(0) of 3.3 T measured at 163 GPa. This work is expected to shed some light on the controversy surrounding superconductivity in the nitrogen‐doped lutetium hydride system.